2019
DOI: 10.3390/catal9040309
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Synthesis Method on the Properties and CO2 Sorption Capacity of UiO-66(Ce)

Abstract: A series of cerium-based UiO-66 was obtained via hydrothermal and sonochemical methods, using the same quantities of reagents (cerium ammonium nitrate (CAN), terephthalic acid (H2BDC)) and solvents) in each synthesis. The impact of synthesis method and metal to linker ratio on the structural and textural properties of obtained UiO-66(Ce), as well as their composition in terms of Ce4+/Ce3+ ratio, structure defects resulting from missing linker, and CO2 adsorption capacity was discussed. By using typical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 62 publications
4
26
1
2
Order By: Relevance
“…As was reported in [36,37] the UiO-66(Ce) was stable only up to 220−240 • C. Also our studies revealed that complete exchange of Zr for Ce in the UiO-66 shifted the temperature of BDC decomposition to ca. 260−280 • C (depending on the synthesis method) which was followed with the collapse of MOF structure [38]. Compared to UiO-66(Zr) and UiO-66(Ce/Zr), a significant decrease in thermal stability, by ca.…”
Section: Characterization Of Uio-66mentioning
confidence: 99%
See 2 more Smart Citations
“…As was reported in [36,37] the UiO-66(Ce) was stable only up to 220−240 • C. Also our studies revealed that complete exchange of Zr for Ce in the UiO-66 shifted the temperature of BDC decomposition to ca. 260−280 • C (depending on the synthesis method) which was followed with the collapse of MOF structure [38]. Compared to UiO-66(Zr) and UiO-66(Ce/Zr), a significant decrease in thermal stability, by ca.…”
Section: Characterization Of Uio-66mentioning
confidence: 99%
“…Catalysts 2019, 9, x FOR PEER REVIEW 9 of 17 ca. 260−280 °C (depending on the synthesis method) which was followed with the collapse of MOF structure [38]. Compared to UiO-66(Zr) and UiO-66(Ce/Zr), a significant decrease in thermal stability, by ca.…”
Section: Characterization Of Uio-66mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Salama et al, reported an SO2 gas sensor while using an MOF [12]. Metal-organic frameworks (MOFs) have a wide range of interesting properties such as high specific surface area and facile modification [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. MOFs are microporous materials that form three-dimensional (3D) crystalline networks, which are prepared by combining various metal ions with organic linkers in an appropriate solvent [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Here we have reported, synthesis, characterization and applications of Ce-MOF. In comparison with the solvothermal and hydrothermal synthesis [6], the stirring route is low cost and environmentally friendly. Hence we successfully synthesized cerium benzene dicarboxylic acid (Ce-bdc) MOF by a simple, cost-effective method with green strategy.…”
Section: Introductionmentioning
confidence: 99%